ANALYZING FACTORS INFLUENCING THE MATHEMATICAL PROBLEM SOLVING ABILITY OF ELEMENTARY SCHOOL STUDENTS - Hanum Faizunnur Lathifah; Henry Suryo Bintoro; Himmatul Ulya (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research analyzed the mathematical problem solving ability of elementary school students. This research was conducted by involving 8 grade IV students. The purpose of this study was to determine the factors affecting the students’ mathematical problem solving abilities. This study used a qualitative approach with the type of case study. The result of this study found 6 factors that affected students’ mathematical problem solving abilities. The factors were (1) the students’ ability to understand the scope of the problem in order to find the solution, (2) the students’ ability to choose a mathematical approach/strategy/model to solve the problem, (3) the students’ ability to give reasons and to solve problems, (4) the students’ self-confidence or doubt when working on problem solving questions, (5) the students’ abilityto process their own data, and (6) the students’ precision in checking the results they obtained. In this study, there were 2 novelty factors found about students’ mathematical problem solving abilities. The first factor was (1 the students’ ability to learn and solve the problem (2) the students’ self-confidence ot doubts when working on problem solving questions.